The identity of the South African toad Sclerophrys capensis Tschudi, 1838 (Amphibia, Anura) - (:unkn) unknown (My University, 2016)
The toad species Sclerophrys capensis Tschudi, 1838 was erected for a single specimen from South Africa which has never been properly studied and allocated to a known species. A morphometrical and morphological analysis of this specimen and its comparison with 75 toad specimens referred to five South African toad species allowed to allocate this specimen to the species currently known as Amietophrynus rangeri. In consequence, the nomen Sclerophrys must replace Amietophrynus as the valid nomen of the genus, and capensis as the valid nomen of the species. This work stresses the usefulness of natural history collections for solving taxonomic and nomenclatural problems.
Keywords: African Research